(untitled) (Mongolian Journal of International Affairs, 2026)
Since declaring independence, Kazakhstan has actively pursued foreign direct investment as a central component of its economic development strategy. Over more than three decades, the country has accumulated an FDI inward stock of approximately USD 151.3 billion, accounting for about 70% of total FDI in Central Asia. Kazakhstan’s position as the region’s leading recipient of foreign investment is shaped by a combination of domestic institutional factors and external geopolitical conditions. This article examines the key features of Kazakhstan’s investment policy, with particular attention to the legal framework, institutional mechanisms, and policy instruments that underpin its investment ecosystem.